2002
DOI: 10.1074/jbc.m104732200
|View full text |Cite
|
Sign up to set email alerts
|

Four Hydrophobic Amino Acids of the Factor VIII C2 Domain Are Constituents of Both the Membrane-binding and von Willebrand Factor-binding Motifs

Abstract: Factor VIII binds to phospholipid membranes and to von Willebrand factor (vWf) via its second C domain, which has lectin homology. The crystal structure of the C2 domain has prompted a model in which membrane binding is mediated by two hydrophobic spikes, each composed of a pair of residues displayed on a ␤-hairpin turn, and also by net positive charge and specific interactions with phospho-L-serine. , and 91% reduction in specific activity in the activated partial thromboplastin time assay. In a phospholipidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 50 publications
8
148
0
2
Order By: Relevance
“…This patch is highly reminiscent of the hydrophobic surface around the spikes observed for both FaV (W26, W27, M83, L79) [10,33] and FaVIII (V2223, M2199, F2200, L2251, L2252) [11,34], which are likely candidates for phospholipid bilayer binding. Membrane involvement seems to be a com- mon feature for several members of the discoidin domain family.…”
Section: Resultsmentioning
confidence: 99%
“…This patch is highly reminiscent of the hydrophobic surface around the spikes observed for both FaV (W26, W27, M83, L79) [10,33] and FaVIII (V2223, M2199, F2200, L2251, L2252) [11,34], which are likely candidates for phospholipid bilayer binding. Membrane involvement seems to be a com- mon feature for several members of the discoidin domain family.…”
Section: Resultsmentioning
confidence: 99%
“…A 1.5-Å x-ray crystal structure of the FVIII C2 domain and a mutagenesis study suggested that two hydrophobic loops formed by Met 2199 -Phe 2200 and Leu 2251 -Leu 2255 play an important role (11,12). Two additional loops formed by Trp 2313 -His 2315 and Gln 2222 -Lys 2227 ) were also proposed to be involved in membrane binding based on an electron microscopy study (13).…”
Section: Blood Coagulation Factor VIII (Fviii)mentioning
confidence: 99%
“…21,22 Mutagenesis studies have confirmed the role of these residues in phospholipid binding. 23,24 The homology of the lactadherin C domains with those of factors VIII and V suggests that similar phospholipid-binding properties may exist. Indeed, lactadherin has been found to bind selectively to PS 25 and to use primarily the C2 domain in its lipid binding.…”
Section: Introductionmentioning
confidence: 99%